Willingness to pay for protecting natural environments in Pulau Redang Marine Park, Malaysia - Mohd Parid Mamat; Mohd Rusli Yacob; Alias Radam; Awang Noor Abdul Ghani; Lim Hin Fui (African Journal of Environmental Economics and Management, 2013)
Although marine parks, national parks, wildlife sanctuaries and reserves are established to conserve biodiversity and enhance ecotourism, some of the country’s protected areas are under threat whether at varying degree. The biggest threat arises from human encroachment. To rescue these resources, appropriate conservation strategy must be put in place. This requires proper valuation of the environment. Taking Pulau Redang Marine Park (PRMP) as a case, information on people’s willingness to pay (WTP) to protect the environment was gathered. Using the dichotomous-choice contingent-valuation method (CVM), it was found that the recreationists are willing to protect the park. The study showed that the average WTP ranged between RM10.86 and RM28.69 that could contribute between RM1.65 million and RM4.36 million in aggregate for the year 2008